Theology as Work: The Mandatum and the Rights of Labor - McCormick, Patrick T. (Horizons, 2002)
Many oppose the mandatum as a threat to the academic freedom of Catholic scholars and the autonomy and credibility of Catholic universities. But the imposition of this juridical bond on working theologians is also in tension with Catholic Social Teaching on the rights and dignity of labor. Work is the labor necessary to earn our daily bread. But it is also the vocation by which we realize ourselves as persons and the profession through which we contribute to the common good. Thus, along with the right to a just wage and safe working conditions, Catholic Social Teaching defends workers' rights to a full partnership in the enterprise, and calls upon the church to be a model of participation and cooperation. The imposition of the mandatum fails to live up to this standard and threatens the jobs and vocations of theologians while undermining this profession's contribution to the church.